IMPLEMENTASI NILAI-NILAI NASIONALISME UNTUK MENANAMKAN PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN TEMATIK MUATAN PENDIDIKAN KEWARGANEGARAAN SISWA KELAS IV SD SE-GUGUS 02 GONDOKUSUMAN - Miritno, Sofilatul Istiqomah; Nadziroh, Nadziroh (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to determine the implementation of nationalism values, inhibiting factors in the implementation of nationalism values, as well as solutions to overcome obstacles implementing nationalism values to instill character education in the subjects of Citizenship Education for fourth-grade students of Elementary School Group 02 Gondokusuman Yogyakarta. The method in this research is qualitative. The data sources in this study are primary data sources and secondary data sources. The subjects of this study were the principal, grade IV teachers, and grade IV, students. The variables in this study are the implementation of the values of nationalism, character education, and thematic learning content of Citizenship Education in class IV Elementary School 02 Gondokusuman Yogyakarta. The data collection methods used observation, interviews, and documentation. The data analysis techniques in the study are data reduction, data presentation, and concluding. The data validity technique is by increasing the persistence and triangulation of sources, triangulation of techniques, and triangulation of time. The results showed that 1) the implementation of the values of nationalism to instill character education in Elementary School 02 Gondokusuman Yogyakarta by directing and practicing it to students. In Civics learning is done by giving examples in daily life and teaching students to respect each other, peers, teachers, and everyone. 2) The thing that hinders this implementation is that it lies in the students themselves, the teacher, the learning environment, and the student's living environment. 3) The solution provided provides examples of good behavior by the teacher during learning and the teacher communicates with students' parents through social media that they have so that when at home parents can better control student behavior.